Hippocampal Dysconnectivity and Altered Glutamatergic Modulation of the Default Mode Network – a Combined Resting State Connectivity and Magnetic Resonance Spectroscopy Study in Schizophrenia - Nelson, Eric A. (Biol Psychiatry Cogn Neurosci Neuroimaging, 2022)
BACKGROUND: Converging lines of evidence point to hippocampal dysfunction in schizophrenia. It is thought that hippocampal dysfunction spreads across hippocampal subfields and to cortical regions by way of long-range efferent projections. Importantly, abnormalities in the excitation/inhibition balance could impair the long-range modulation of neural networks. The goal of this project was twofold. First, we sought to identify replicable patterns of hippocampal dysconnectivity in patients with a psychosis spectrum disorder, and second we aimed to investigate a putative link between glutamatergic metabolism and hippocampus connectivity alterations. METHODS: We evaluated resting state hippocampal functional connectivity alterations in two cohorts of patients with a psychosis spectrum disorder: the first consisted of 55 medication-naïve first episode psychosis (FEP) subjects and 41 matched healthy controls (HC), and the second consisted of 42 unmedicated patients with schizophrenia and 41 matched controls. We also acquired measurements of glutamate + glutamine (Glx) in the left hippocampus using magnetic resonance spectroscopy for 42 FEP and 37 HC from our first cohort. RESULTS: We observed a pattern of hippocampal functional hypoconnectivity to regions of the default mode network (DMN) and hyperconnectivity to lateral occipital cortex in both cohorts. We also show that, in HC, greater hippocampal Glx levels predicted greater hippocampal functional connectivity to the anterior DMN. Furthermore, this relationship was reversed in medication-naïve FEP subjects. CONCLUSION: These results suggest that an alteration in the relationship between glutamate and functional connectivity may disrupt the dynamic of major neural networks.